A citizen science survey discloses the current distribution of the endangered Yellow Cardinal Gubernatrix cristata in Argentina. Issue 1 (20th March 2021) - DOMÍNGUEZ, MARISOL; LAPIDO, ROCÍO; GORRINDO, ADRIÁN; ARCHUBY, DIEGO; CORREA, EMILIO; LLANOS, FABIÁN; REALES, FABRICIO; PIANTANIDA, FABRIZIO; MARATEO, GERMÁN; MERIGGI, JORGE; ANDREANI, LUCAS; ENCABO, MANUEL; et al.
Summary: The Yellow Cardinal Gubernatrix cristata is a globally endangered passerine from the southern cone of South America. Because of its conspicuous plumage and very attractive song, it suffers considerably from illegal pet trade. The largest remaining populations are found in Argentina, but no coordinated efforts have been made thus far to understand better its current distribution and conservation status. During three annual surveys supported by a citizen science programme, more than 140 volunteers surveyed 644 geographical points during spring and detected 221 Yellow Cardinals. Based on the survey results, we evaluated the presence of cardinals within protected areas in Argentina and found that the species was only detected in four of them, two of which were private reserves with a low level of protection. We also found that the species was not restricted to the 'Espinal' ecoregion, but also inhabited 'Monte' and 'Chaco' ecoregions, which are generally drier. This citizen science programme allowed us to obtain up-to-date information on the remaining populations of the Yellow Cardinal and helped to increase public awareness about the conservation problems faced by the species. We propose some future strategies for monitoring Yellow Cardinals and taking informed conservation decisions.